1992
DOI: 10.1037/1040-3590.4.4.426
|View full text |Cite
|
Sign up to set email alerts
|

Relative usefulness of elevation, variability, and shape information from WISC—R, K-ABC, and Fourth Edition Stanford-Binet profiles in predicting achievement.

Abstract: Scatter analysis of IQ profiles has a long and controversial history. We conducted this study to determine whether the validity of scatter information is any greater for 2 new IQ batteries, the Kaufman Assessment Battery for Children (K-ABC) and the Fourth Edition Stanford-Binet (SB4), than for the Wechsler Intelligence Scale for Children-Revised (WISC-R). Within a sample of referred children, we computed numerical indexes of profile elevation, shape, and variability for all IQ tests. Using hierarchical multip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 22 publications
2
9
0
Order By: Relevance
“…The results reported by Watkins and Glutting (2000) comport closely with those reported by Hale and Saxe (1983) and Kline et al (1992). Beyond two robust, but somewhat uninformative profiles, WISC-III subtest profile scatter and shape information had inconsequential incremental validity for predicting reading and math achievement for students with and without exceptionalities.…”
Section: Modal Wisc-lll Profilessupporting
confidence: 74%
See 1 more Smart Citation
“…The results reported by Watkins and Glutting (2000) comport closely with those reported by Hale and Saxe (1983) and Kline et al (1992). Beyond two robust, but somewhat uninformative profiles, WISC-III subtest profile scatter and shape information had inconsequential incremental validity for predicting reading and math achievement for students with and without exceptionalities.…”
Section: Modal Wisc-lll Profilessupporting
confidence: 74%
“…Systematic examination of ACID and SCAD profiles in addition to the Developmental Index and the Profile Variability Index demonstrated that they were little better than chance when used to differentiate children with exceptionalities (Watkins, 1996, 1999; Watkins, Kush, & Glutting, 1997a, b). Beyond diagnosis, cognitive profiles have not provided substantial incremental validity for prediction of academic achievement (Glutting, Youngstrom, Ward, Ward, & Hale, 1997; Hale & Saxe, 1983; Kline, Snyder, Guilmette, & Castellanos, 1992; Watkins & Glutting, 2000; Youngstrom, Kogos, & Glutting, 1999) and have not beneficially contributed via hypothetico-deductive approaches to interpretation (Kramer et al, 1987). A particularly blunt appraisal of the research literature was provided by Kavale and Forness (1984), who concluded that “profile and scatter analysis is not defensible” (p. 136).…”
Section: Existing Evidence Regarding Profile Analysismentioning
confidence: 99%
“…Review of the literature on subtest analysis validity and utility (Watkins, 2003;Watkins, Glutting, & Youngstrom, 2005) showed that subtest scores, patterns, and analyses were unable to adequately identify global neurocognitive or neuropsychological defi cits presumably related to learning disability (Watkins, 1996), nor were they related to or valid for diagnosis of learning disabilities (Daley & Nagle, 1996;Glutting, McGrath, Kamphaus, & McDermott, 1992;Hale & Raymond, 1981;Hale & Saxe, 1983;Kahana et al, 2002;Kavale & Forness, 1984;Kline, Snyder, Guilmette, & Castellanos, 1992;Livingston et al, 2003;Maller & McDermott, 1997;Mayes, Calhoun, & Crowell, 1998;McDermott, Goldberg, Watkins, Stanley, & Glutting, 2006;McGrew & Knopik, 1996;Mueller, Dennis, & Short, 1986;Ree & Carretta, 1997;Smith & Watkins, 2004;Th orndike, 1986;Ward, Ward, Hatt, Young, & Mollner, 1995;Watkins, 1999Watkins, , 2000Watkins, , 2003Watkins, , 2005Watkins & Glutting, 2000;Watkins & Kush, 1994;Watkins, Kush, & Glutting, 1997a, 1997bWatkins, Kush, & Schaefer, 2002;Watkins & Worrell, 2000). Furthermore, subtest analyses were not valid in the classifi cation of behavioral, social, or emotional problems (Beebe, Pfi ff ner, & McBurnett, 2000;…”
Section: Ipsative Subtest Comparisonsmentioning
confidence: 99%
“…Although the eight core profile types differed significantly across external measures of achievement and receptive vocabulary, most of the explained variance was due to differences in elevation and not shape (i.e., sequential versus simultaneous). Results of other studies conducted with much smaller samples of normal, referred, or learning disabled children (Das & Mensink, 1989;Kempa, Humphries, & Kerschner, 1988;Kline, Snyder, Guilmette, & Castellanos, 1992, 1993McRae, 1986) indicate a similar conclusion: The shapes of children's K-ABC profiles are not strongly related to levels of scholastic achievement.…”
Section: Lessons From the K-abc's Interpretive Modelmentioning
confidence: 79%
“…poor school performance (e.g., Kline et al, 1992;Richman & Lindgren, 1980), but this observation is hardly a revelation: School success obviously requires adequate language-related skills.…”
Section: Broader Lessons From the K-abc's Ability-achievement Modelmentioning
confidence: 99%